Idiopathic Pulmonary Fibrosis: A Narrative Literature Review - Febrina, Nidya; Dewi Wijaya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Idiopathic pulmonary fibrosis is a chronic progressive interstitial lung disease (ILD) with unknown causes. Male gender, age > 60 years, history of smoking with symptoms of dry cough and progressive chronic shortness of breath are typical clinical findings in this patient. The diagnosis is made based on a combination of radiological findings in the form of a pattern consistent with usual interstitial pneumonia (UIP) and/or histopathology with the exclusion of other causes of ILD. Treatment includes pharmacological and non-pharmacological therapy in the form of pulmonary rehabilitation, psychosocial support, and lung transplantation. Anti-fibrosis pharmacological therapy, namely nintedanib and pirfenidone, has been proven to slow the progression of pulmonary fibrosis and reduce mortality. The relatively low average survival rate of 3-4 years after the diagnosis is made makes this disease have a poor prognosis and requires adequate identification and treatment in order to reduce morbidity, mortality and improve the quality of life of sufferers.